2023
DOI: 10.1098/rspb.2022.1966
|View full text |Cite
|
Sign up to set email alerts
|

Travelling with a parasite: the evolution of resistance and dispersal syndromes during experimental range expansion

Abstract: Rapid evolutionary change during range expansions can lead to diverging range core and front populations, with the emergence of dispersal syndromes (coupled responses in dispersal and life-history traits). Besides intraspecific effects, range expansions may be impacted by interspecific interactions such as parasitism. Yet, despite the potentially large impact of parasites imposing additional selective pressures on the host, their role on range expansions remains largely unexplored. Using microcosm populations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…Our study reinforces the value of biological invasions as model systems in which to explore rapid evolutionary changes not only in invasive species and the native biota affected by them [10], but also in co-adapted interactions among species [48]. Invasive host-parasite systems are ideal in this respect, because the novel evolutionary pressures engendered by range expansion can result in rapid shifts in adaptive optima for both participants in the arms race [11]. In the case of cane toads in Australia, invasion has produced striking disparities in the ability of co-evolved lungworms to infect their hosts, and in the ability of those hosts to resist infection.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our study reinforces the value of biological invasions as model systems in which to explore rapid evolutionary changes not only in invasive species and the native biota affected by them [10], but also in co-adapted interactions among species [48]. Invasive host-parasite systems are ideal in this respect, because the novel evolutionary pressures engendered by range expansion can result in rapid shifts in adaptive optima for both participants in the arms race [11]. In the case of cane toads in Australia, invasion has produced striking disparities in the ability of co-evolved lungworms to infect their hosts, and in the ability of those hosts to resist infection.…”
Section: Discussionsupporting
confidence: 73%
“…An absence of native-range parasites (enemy release) in the newly colonized area can facilitate the success of an invasion by allowing individuals of the translocated species to redirect resources from parasite defence into dispersal, growth, reproduction and competitive ability [12,13]. By contrast, high rates of parasitism by native-range or newly encountered parasite taxa can slow an invasion if infection reduces dispersal rate or entails energy allocation for immune defence [11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the increase in equilibrium density might be an emergent property. Indeed, previous work on another ciliate ( Tetrahymena ) shows that evolution in the presence of relatively slowly growing food bacteria can promote more prudent consumption rates ( Fronhofer & Altermatt, 2015 ), thus associating lower maximum population growth rate (selected trait) with higher equilibrium density (emergent trait; see also Zilio et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental evolution and microcosm landscapes have been used to test fundamental predictions and mimic range expansions in the laboratory. Experiments with ciliates ( Fronhofer & Altermatt, 2015 ; Zilio et al, 2023 ), arthropods ( Ochocki & Miller, 2017 ; Petegem et al, 2018 ; Szűcs et al, 2017 ; Weiss-Lehman et al, 2017 ), or plants ( Williams et al, 2016 ) showed the rapid evolution of dispersal and other dispersal-related traits during the experimental range expansions, such as growth, size, locomotory capacity, or exploratory behavior. However, whether we can accurately predict these processes and the accompanying trait evolution from prior information on the genetic or phenotypic characteristics of the expanding populations remains an open question ( Angert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%